Institutional Logics and Community Service-Learning in Higher Education - Taylor, Alison; Kahlke, Renate (Canadian Journal of Higher Education, 2017)
This paper explores how community service-learning (CSL) participants negotiate competing institutional logics in Canadian higher education. Drawing theoretically from new institutionalism and work on institutional logics, we consider how CSL has developed in Canadian universities and how participants discuss CSL in relation to other dominant institutional logics in higher education. Our analysis suggests participants’ responses to competing community, professional, and market logics vary depending on their positions within the field. We see actors’ use of hybrid logics to validate community-engaged learning as the strategy most likely to effect change in the field.